1986
DOI: 10.1115/1.3143705
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelasticity with Second Sound: A Review

Abstract: Thermoelasticity theories predicting a finite speed for the propagation of thermal signals have come into existence during the past 20 years. In contrast to the conventional thermoelasticity theory, these nonclassical theories involve a hyperbolic-type heat transport equation, and are motivated by experiments exhibiting the actual occurrence of wave-type heat transport (second sound). Several authors have formulated these theories on different grounds, and a wide variety of problems revealing characteristic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
312
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 808 publications
(318 citation statements)
references
References 0 publications
3
312
0
3
Order By: Relevance
“…However, determining u and for arbitrary t is a tedious task. Since the second-sound effects are short lived [4], it may be sufficient to obtain and analyse the solutions for small t. This is done by taking s to be large.…”
Section: Transform Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, determining u and for arbitrary t is a tedious task. Since the second-sound effects are short lived [4], it may be sufficient to obtain and analyse the solutions for small t. This is done by taking s to be large.…”
Section: Transform Solutionmentioning
confidence: 99%
“…In view of the experimental evidence available in favour of finiteness of heat propagation speed, generalized thermoelasticity theories are considered to be more realistic than the conventional thermoelasticity theory in dealing with practical problems involving very large heat fluxes at short intervals, like those occurring in laser units and energy channels. For a review of the relevant literature, see [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well-known that due to its parabolic character it implies infinite speed of the signal propagation and thus should be modified if very large gradients or extremely small scales are involved [17][18][19][20]. On macroscopic level, numerous modifications were suggested to recover the hyperbolic character of the heat transport equation [19][20][21][22]. Perhaps, the most known is the lowest -order approximation known as CattaneoVernotte (CV) or telegraphist (TE) law [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…These nonclassical theories are often regarded as the generalized dynamic theory of thermoelasticity. Brief reviews of this topic have been reported by Chandrasekharaiah [4]. The phenomenon of reflection of pure elastic waves may be found in many references [1,2,5,6,10,13].…”
Section: Introductionmentioning
confidence: 99%